Management research : guide for institutions and professionals - Bennett, Roger (Geneva : International Labour Office, 1983)
This book reflects the collective experience and thinking of many institutions, centres and schools that are keen to improve management research. It deals with the purpose and nature of management research; research policy and planning; the choice of research methods; organizing research; disseminating and using research results; and developing competent researchers.
Includes bibliographical references.
hza 30/07/2018
Loans
Keywords: Management; Production management; Research